2008
DOI: 10.1128/jcm.00505-08
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Norovirus Diarrhea in Nicaragua

Abstract: Information about norovirus (NoV) infections in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
86
3
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 32 publications
13
86
3
3
Order By: Relevance
“…This is due to norovirus causing less severe diarrhoea than rotavirus and parents tend not to seek medical services [25,26]. In our study, the severity of diarrhoea episodes was similar in children with and without NoV and similar high detection rates had been reported from Chile, India and Nicaragua at that time when the vaccines had not been introduced [18][19][20].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is due to norovirus causing less severe diarrhoea than rotavirus and parents tend not to seek medical services [25,26]. In our study, the severity of diarrhoea episodes was similar in children with and without NoV and similar high detection rates had been reported from Chile, India and Nicaragua at that time when the vaccines had not been introduced [18][19][20].…”
Section: Discussionsupporting
confidence: 82%
“…Globally, hospital-based series in children with diarrhoea report a median of 14%, which seems lower than the proportions detected in our study [17]. Although our data suggests an annual increase in the proportion of cases, similar detection rates had been reported from Chile, India and Nicaragua prior to rotavirus vaccine introduction [18][19][20]. This relative increase may also be due to the decrease of number of rotavirus-related hospitalizations [10,11] and all-cause diarrhoea cases due to the effectiveness of the rotavirus vaccine [21] and the herd effect of the vaccine that has resulted in an overall and not a real increase in the overall number of NoV cases.…”
Section: Discussioncontrasting
confidence: 60%
“…In other recent studies GII.4 strains were detected even more frequently ranging from 62.7% to 68%. 13,36,37 This is the first report of GII. 4 The data suggests that 80% of the NoV infections in this study were community acquired.…”
Section: Discussionmentioning
confidence: 79%
“…These results are similar to studies in Brazil, Nicaragua and Tunisia where the predominance of the GII strains in hospitalised children with gastroenteritis (88-96% of NoV positive specimens) was also noted. 13,36,37 However, other studies in Brazil 39 and Mexico 40 found GI and GII strains at comparable frequencies. These studies were conducted over different time intervals several years ago (1998 and 1998-2005) and used different study populations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation